Penerapan Manajemen Risiko Pada Destinasi Wisata Sungai Palayangan Cileunca, Kabupaten Bandung - Ariya Aurel Megantara; Muhammad Faishal Rabbani Zahran (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2025)
This research is to identify and evaluate risk management practices in tourist destinations in order to improve sustainability and tourist safety. The tourism industry is mandated to adopt risk management as it seeks to maintain the good reputation of the destination, increase tourist attraction, and instill confidence that tourists will return to the destination. This is being done. With the increasing number of tourists, environmental and health risks have become a major concern for the management of tourist destinations. This research methodology uses descriptive qualitative primary data obtained from direct field observations and interviews. Data was collected through in-depth interviews with destination managers, tourist surveys, and analysis of relevant policy documents. The findings show that there is systematic risk management in place, including identifying potential risks of accidents and environmental damage. The study shows that regular staffing and collaboration with local stakeholders are important for maintaining long-term sustainability. Effective risk management enables tourist destinations to provide safer and higher-quality experiences for tourists. Risk management practices implemented include pre-tour safety briefings, provision of life jackets, and cancellation of tours in case of heavy rain or wildlife presence. Management control initiatives already exist but have not been optimized.